P1402Isolation of pulmonary veins with duty-cycled circular multi-polar catheter: randomized controlled clinical trial. (18th June 2020) - De Sousa, J; Cortez-Dias, N; Carpinteiro, L; Silva, G; Nunes Ferreira, A; Silverio Antonio, P; Bernardes, A; Barreiros, C; Ribeiro, J; Sobral, S; Pinto, F
Abstract: Introduction: Pulmonary vein isolation (PVI) is the central element in the ablation of atrial fibrillation (AF), and can be obtained with different ablation modalities. The duty-cycled circular multi-pole catheter PVAC® (Medtronic) allows linear application of radiofrequency energy, with the production of circumferential lesions. Conceptually, it can make ablation simpler and faster in patients with favorable anatomy. Objectives: To evaluate the safety and efficacy of ablation with a PVAC® catheter and to compare it with the conventional technique point-by-point (PbP) with irrigated catheter. Methods: Clinical trial with single-blinded patients with AF refractory to antiarrhythmic therapy, randomized (1: 1) for ablation with PVAC® or PbP. The ablation strategy consisted of PVI, complemented with ablation of the cavo-tricuspid isthmus in patients with history of concomitant flutter. Monitoring was performed with a 7-day event loop recorder at 3, 6 and 12 months and annually from the 2nd year. Success was defined by AF-free survival or any maintained supraventricular tachycardia (duration > 30seconds). Results: 354 patients (67.5% males, 58 ± 12 years, PbP: 175, PVAC: 179) were included, of which 59.1% had paroxysmal, 26.2% short-standing persistent and 14.7% had long-standing persistent AF. Baseline characteristics were similar between groups. Among patients treated with PVAC, 93.1% of the pulmonary veins were isolated (620/666), similar to the 98.3% immediate success of the PbP group (697/709). Although the complication rate was similar in both groups (PVAC: 4.9% vs. PbP: 7.8%; P = NS), the risk of hemopericardium was lower with PVAC (0% vs. 4.6%; P = 0.013). Two patients treated with PVAC developed stroke (1.13% vs. 0%; P = NS). The duration of the procedure was lower among the patients treated with PVAC [136 (100-180) vs. 230 (188-270) min; P <0.001], with no difference in fluoroscopy time [24.4 (14.5-36.8) vs. 27.1 (17.0-45.0) min]. The success rate after 1st ablation at 36 months was 68%, with no differences between groups. The success rate after multiple ablations increased to 85.8%, with no differences between groups. Conclusion: The multipolar PVAC catheter can represent an added value in AF ablation, making the procedure simpler and faster, ensuring similar efficacy to the conventional technique and with a lower risk of cardiac tamponade. The present trial suggests the need for clinically manifested stroke risk surveillance, which may be increased with this technique.